Nurses' perceptions of adolescents accessing and utilizing sexual and reproductive healthcare services in Cape Town, South Africa: A qualitative study. (September 2019) - Jonas, Kim; Roman, Nicolette; Reddy, Priscilla; Krumeich, Anja; van den Borne, Bart; Crutzen, Rik
Abstract: Background: In Sub-Saharan Africa access to and utilization of sexual and reproductive healthcare is unsatisfactory. Consequently, rates of teenage pregnancy and unsafe abortions among adolescents in Sub-Saharan Africa, including in South Africa remain a public health challenge. The aim of this study was to explore nurses' views on and perceptions of adolescent girls' barriers and needs to accessing and utilizing sexual and reproductive healthcare services. Methods: Twenty-four purposively selected healthcare workers from nine public healthcare facilities in Cape Town, South Africa participated in this qualitative descriptive study. Data were collected through nine group discussions, and audio-recorded with hand-written notes taken during the discussions. Data were analyzed using thematic analysis, following the Tesch's eight steps for coding and analysing qualitative data. Results: Sexual and reproductive healthcare nurses are generally supportive of adolescents who ask for and use contraceptives. Non-compliance to family planning regimens and repeated requests for termination of pregnancies were perceived by nurses as irresponsible behaviours which are particularly frustrating to them and not in concordance with their personal values. The subsequent nurse-adolescent interactions sometimes appeared to hinder access to and utilization of sexual and reproductive healthcare services by adolescents. Conclusions: Nurses perceive certain behaviours of adolescent girls as irresponsible and warrant their negative attitudes and reactions toward them. The negative attitudes and reactions of nurses potentially further compromises access to and utilization of sexual and reproductive healthcare services by adolescent girls in South Africa and requires urgent attention. Adolescent-friendly clinic hours together with youth-friendly nurses is likely to encourage adolescent girls to access sexual and reproductive healthcare services and improve the use thereof.